Polymer melt rheology : a guide for industrial practice - Cogswell, F. N. (Woodhead Pub., 1994)
This book explores the ways in which melt flow behaviour can be exploited by the plastics engineer and technician for increased efficiency of processing operation, control of end product properties and selection and development of polymers for specific purposes. (reissued with minor corrections 1994).